Gender, hormone therapy, and HIV: what should cardiologists know? - Martinez, C. A. (Neth Heart J, 2019)
Transgender individuals represent the fastest growing minority in the United States and are disproportionately affected by HIV. Hormone therapy is the most common treatment for gender dysphoria in transgender individuals. As HIV is an independent risk factor for coronary artery disease, it is critical to further research the influence masculinising and feminising hormone therapies have on cardiovascular disease. There is a clinical need for evidence-based guidelines for cardiologists to follow to effectively care for and treat transgender patients. For this to be done, the interplay between HIV, hormone therapy, and cardiovascular disease must be better understood through collaboration between researchers and clinicians to achieve maximum benefit from recent advancements.